Comparison of CD8+ T Cell Accumulation in the Brain During Human and Murine Cerebral Malaria - Barrera, Valentina; Haley, Michael J.; Strangward, Patrick; Attree, Elizabeth; Kamiza, Steve; Seydel, Karl B.; Taylor, Terrie E.; Milner, Danny A.; Craig, Alister G.; Couper, Kevin N. (Frontiers in Immunology, 2019)
CD8+ T cells have been shown to play a critical role in the pathogenesis of experimental cerebral malaria (ECM) in mice, but their role in development of human cerebral malaria (HCM) remains unclear. Thus, in this study we have provided the first direct contrast of the accumulation of CD8+ T cells in the brain during HCM and ECM. HCM cases were from children who died of Plasmodium falciparum cerebral malaria at Queen Elizabeth Central Hospital (Malawi) between 2003 and 2010. ECM was induced by infecting C57BL/6J mice with P. berghei ANKA. We demonstrate similarities in the intracerebral CD8+ T cell responses in ECM and HCM, in particular an apparent shared choroid plexus – meningeal route of CD8+ T cell accumulation in the brain. Nevertheless, we also reveal some potentially important differences in compartmentalisation of CD8+ T cells within the cerebrovascular bed in HCM and ECM.